Materials Chemistry - Fahlman, Bradley D. (Springer Netherlands : Imprint: Springer, 2007)
-A new expanded and updated edition of this book is expected Spring 2011- Winner of a 2008 Textbook Excellence Award from the Text and Academic Authors Association (TAA)! Written to fill the need for a textbook that addresses inorganic-, organic-, and nano-based materials from a structure vs. property treatment, Materials Chemistry aims to provide a suitable breadth and depth coverage of the rapidly evolving materials field -- in a concise format. This modern treatment offers innovative coverage and practical perspective throughout, e.g.: the opening solid-state chemistry chapter uses color illustrations of crystalline unit cells and digital photos of models to clarify their structures, plus an ample amorphous-solids section; the metals chapter treats the full spectrum of powder metallurgical methods, complex phase behaviors of the Fe-C system and steels, and topics such as corrosion and shape-memory properties; the semiconductor chapter addresses evolution and limitations/solutions of modern transistors, as well as IC fabrication and photovoltaics; the polymer and ‘soft’ materials chapter describes all polymeric classes including dendritic polymers, as well as important additives such as plasticizers and flame-retardants, and emerging applications such as molecular magnets and self-repairing polymers; final chapters on nanomaterials and materials-characterization techniques are also carefully surveyed, focusing on nomenclature, synthetic techniques, and applications taken from the latest scientific literature. Most appropriate for Junior/Senior undergraduate students, as well as first-year graduate students in chemistry, physics, or engineering fields, Materials Chemistry may also serve as a valuable reference to industrial researchers. Each chapter concludes with a section that describes important materials applications, while appendices include laboratory modules for materials synthesis and a comprehensive timeline of major materials developments.